Polypharmacology in drug discovery - Peters, Jens-Uwe (Wiley, 2012)
"Covers the two-sided nature of polypharmacology--its contribution to adverse drug reactions and its benefit in certain therapeutic drug classes. Addresses the important topic of polypharmacology in drug discovery, a subject that has not been thoroughly covered outside of scattered journal articles Overviews state-of-the-art approaches and developments to help readers understand concepts and issues related to polypharmacology"--Provided by publisher.